The role of physical workload and pain related fear in the development of low back pain in young workers: evidence from the BelCoBack Study; results after one year of follow up. Issue 1 (16th December 2005) - Van Nieuwenhuyse, A; Somville, P R; Crombez, G; Burdorf, A; Verbeke, G; Johannik, K; Van den Bergh, O; Masschelein, R; Mairiaux, Ph; Moens, G F
Abstract : Aims: To study the influence of work related physical and psychosocial factors and individual characteristics on the occurrence of low back pain among young and pain free workers. Methods: The Belgian Cohort Back Study was designed as a prospective cohort study. The study population of this paper consisted of 716 young healthcare or distribution workers without low back pain lasting seven or more consecutive days during the year before inclusion. The median age was 26 years with an interquartile range between 24 and 29 years. At baseline, these workers filled in a questionnaire with physical exposures, work related psychosocial factors and individual characteristics. One year later, the occurrence of low back pain lasting seven or more consecutive days and some of its characteristics were registered by means of a questionnaire. To assess the respective role of predictors at baseline on the occurrence of low back pain in the following year, Cox regression with a constant risk period for all subjects was applied. Results: After one year of follow up, 12.6% (95% CI 10.1 to 15.0) of the 716 workers had developed low back pain lasting seven or more consecutive days. An increased risk was observed for working with the trunk in a bent and twisted position for more than two hours a day (RR 2.2, 95% CI 1.2 to 4.1), inability to change posture regularly (RR 2.1, 95% CI 1.3 to 3.5), back complaints in the year before inclusion (RR 1.7, 95% CI 1.1 to 2.8), and high scores of pain related fear (RR 1.8, 95% CI 1.0 to 3.1). Work related psychosocial factors and physical factors during leisure time were not predictive. Conclusion: This study highlighted the importance of physical work factors and revealed the importance of high scores of pain related fear in the development of low back pain among young workers.